Linagliptin: A thorough Characterization beyond Its Clinical Efficacy - Sortino, Maria Angela; Sinagra, Tiziana; Canonico, Pier Luigi (Frontiers in Endocrinology, 2013)
Linagliptin, one of the five dipeptidyl peptidase-4 inhibitors available, has recently entered the market both in the US and in most European countries for treatment of type 2 diabetes mellitus. It presents a xanthine-based structure, and is characterized by unique pharmacokinetics, with non-linear profile, long terminal half-life allowing prolonged exposure to the drug. It is eliminated predominately through the intestinal tract and only minimally into urine, so that it can be administered, without any dose adjustment, in conditions of renal impairment. Linagliptin is effective in modifying all parameters of hyperglycemia either in monotherapy, or as add-on therapy, together with metformin or a sulfonylurea. It also exhibits a good tolerability profile with few side effects, absence (when used in monotherapy), or low risk (when in combination with a sulfonylurea) of hypoglycemia. More importantly it has a weight neutral effect. A comprehensive report of the literature on linagliptin is provided, paying attention in particular to preclinical studies, interactions with other drugs, safety and tolerability, and results obtained in animal models that highlight properties of linagliptin suggestive of potential additional uses. Particularly promising appear the data demonstrating a positive effect of linagliptin on metabolic dysfunction and renal and/or cardiovascular damage together with more recently reported effects of linagliptin on tissue repair and neuroprotection.